Vladislav Vančura v literárním kontextu 20. století - Poláček, Jiří (Masaryk University Press, 2022)
Title in English: Vladislav Vančura in the Literary Context of the 20th Century On June 23, 2021, it was the 130th anniversary of Vladislav Vančura's birth, and June 1, 2022, was the 80th anniversary of his death. These anniversaries became the impetus for a collective volume entitled Vladislav Vančura in the Literary Context of the 20th Century. The editor Jiří Poláček approached researchers from various disciplines from literary studies to linguistics and to theatre studies with an appeal to think and rethink the literary and general cultural legacy of this important figure. The book volume by the team of researchers from six Czech universities is an attempt to reflect on the oeuvre by Vančura from the perspective of the current state of knowledge in literary studies and the broader context of the 20th century. The image of Vladislav Vančura within the context of the previous century arises from 15 texts by 15 authors, organized into four thematic blocks.